The Influence of Knowledge Management Effectiveness and Organizational Culture on the Performance of Buddhist Sunday School Teachers in Makassar - Suzanna Suzanna; Liana The; Adrian Adrian (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to identify the influence of management effectivenessthe influence of knowledge and organizational culture on the performance of teachers in schoolsSunday Buddhist Schools (SMB) spread across the Makassar region. The independent variables in this study are the effectiveness of knowledge management (X1) and organizational culture (X2), while the dependent variable is teacher performance (Y). The analytical approach used in this study is multiple linear regression to examine the contribution of each independent variable to teacher performance. The sample was determined using a probability sampling technique, with a total of 86 respondents. Primary data was obtained through a questionnaire distributed online via Google Form. Hypothesis testing was conducted using SPSS software version 20.0 for Windows. The results of the studyThis study demonstrates that effective knowledge management and organizational culture play a significant role in improving the performance of Buddhist Sunday School teachers in Makassar City. Well-managed knowledge management can help teachers access, manage, and utilize relevant information to support learning activities. Meanwhile, a supportive organizational culture fosters a harmonious work environment, increases motivation, and strengthens teachers' commitment to their responsibilities as educators. Simultaneously, these two factors complement each other in creating conditions conducive to improving teacher performance.